Análise da permeabilidade dentinária após irradiação com o laser de nd:yag associado a adesivo universal e diferentes biovidros. - PENHA, Karla Janilee De Souza (2016)
The search for materials that decrease dentin permeability (P), has become increasingly relevant due to the increasing prevalence of dentin hypersensitivity (HSD). The use of bio-glasses may be an effective alternative due to bioactivity, as well as the universal adhesives, which may have their optimized effects when associated with Nd: YAG laser, but its clinical application lacks further studies. In Chapter I, the influence of the Nd: YAG (L) laser associated to the two bioglasses (45S5-Silica-Si and NbG-Niobophosphate) investigated was in vitro. Fifty discs of bovine dentin with 6 mm diameter and 1 mm thickness made.were A (P) measured was in 4 moments: with the presence of the smear layer, maximum opening of the tubules, after the treatment and followed by the erosive challenge with the aid of the permeability apparatus (divided chamber model-ODEME). The specimens were randomly distributed in 5 experimental groups (n = 10), according to the treatment performed: (L) in the parameters 60mJ, 10 Hz, 0,6 W and 80mJ, 10 Hz, 0,8 W associated to the bioglass of Si (Si60 and Si80), NbG bioglass, (NbG60 and NbG80) and Control (C). Some specimens selected were for scanning electron microscopy (SEM) and dispersive x-ray spectrometry (EDS). The percentage variations of (P) after the different treatments and erosion obtained were by Kruskal Wallis test with Dunn post hoc test (p> 0.05). It found was that the groups with Si showed a greater decrease of (P). The 45S5 showed a greater decrease of (P) values compared to the groups treated with NbG, Si80 (26.12 ± 8.16) - Si60 (42.20 ± 9.39)> NbG80 (46.28 ± 9.39)> NbG60 (74.63 ± 9.68). Treatments are resistant to erosion when compared to group (C). The SEM and EDS analysis proved the formation of a bioactive layer and all the groups showed resistance to the erosive challenge. NbG and 45S5 when associated to Nd: YAG (60 / 80mJ), showed a significant reduction of (P), since the 45S5 bioglass seemed to promote a greater reduction of (P) in relation to NbG. In Chapter II, the influence of Universal Adhesion (3M ESPE) to (L) for the decrease of (P) was investigated in vitro. 40 dentin disks were made and (P) measured in the same way as the previous study. A60 - Adhesive + Nd: YAG (60mJ, 10Hz, 0.6W), A80 - Adhesive + Nd: YAG (80mJ, 10Hz) were randomly distributed in 4 experimental groups (n = 10) , 0.8 W) AU - Adhesive only and C-Control (without treatment) and then submitted to the erosive challenge. Some samples were prepared for evaluation in (SEM) and (EDS). Kruskal Wallis and Dunn's post hoc tests (p> 0.05) showed that there was no statistical difference between the AU, A60 and A80 groups. After erosive challenge, all treatments were resistant. The use of the Universal adhesive system on the dentin, as well as its association with Nd: YAG laser (60 and 80mJ), presented similar reduction of dentin permeability and resistance to erosive challenge.